Determination Of Novel Antibacterial Triazolylmethyl Oxazolidinones Concentrations In Human Plasma By APCI-LC-MS: Application To Stability Study - Phillips, Oludotun A.; Abdel-Hamid, Mohammed E. (Journal of Pharmacy & Pharmaceutical Sciences, 2008)
Triazolylmethyl oxazolidinones are novel potent antibacterial agents recently synthesized in our laboratory. PURPOSE. Development of a rapid and specific LC-MS method for evaluating the stability of three potentially active antibacterial triazolylmethyl oxazolidinone compounds, namely PH-27, PH-38 and PH-41, in human plasma. METHODS. Ion-trap mass spectrometry using +APCI-MS at m/z 348.1 (PH-27), 389.1 (PH-38) and 451.1 (PH-41) combined with liquid chromatographic analysis using C18 reversed-phase column and a mobile phase consisting of 20 mM ammonium acetate solution and acetonitrile (50:50 v/v) was used. Plasma samples were pre-treated with acetonitrile to precipitate proteins prior to LC-MS analysis. Linezolid was used as an internal standard whose predominant ion at m/z 338.1 was monitored and used to construct the calibration curves. An accelerated stability study under controlled experimental conditions was conducted at -20 oC for a 5-weeks period. RESULTS. Calibration curves of the examined oxazolidinones in human plasma were established (r: 0.99) up to the concentration of 20.0 µg ml-1 with LLQ of 0.1 (PH-27), 0.5 (PH-38) and 1.0 µg ml-1 (PH-41). Validation data showed appropriate intra- and inter-day precision and accuracy as indicated from RSD% 1.3 - 8.6 and % DEVs -12.7 to +11.3, respectively. Stability studies gave the kinetic degradation parameters of kdeg 0.0191- 0.0857 week-1, t1/2 8.1-36.3 weeks and t90 1.2 -5.5 weeks. CONCLUSIONS. The developed +APCI-LC-MS assay is simple, fast and specific method that could be applied for the routine analysis of the selected oxazolidinones during stability and pharmacokinetic studies. The examined compound PH-27 was proved to be relatively more stable and resistant to degradation in human plasma compared to PH-38 and PH-41, as indicated from the kinetics and recovery studies at -20 oC.